Macromolecular distribution of a mixed system on dodol ulame by Confocal Laser Staining Microscopy (CLSM) - Gusti Setiavani; Sugiyono; Adil Basuki Ahza; Nugraha Edhi Suyatma; Jamyang Tashi Wangdi (jurnal1, 2022)
The aim of this study was to learn more about the macromolecular distribution of the food matrix system in the traditional food Dodol Ulame in order to better understand the interactions between starch, fat and sugar. Microstructural stages included dye selection, staining/coloring, material mixing, and observation. The starch was stained with APTS and the fat with Nile red. The starch was stained using the double staining method with covalent labeling. The samples were analyzed with a Zeiss Inverted LSM 800 AXIO Observer equipped with an AXIO cam 503 color camera and an excitation wavelength of 665 nm and 543 nm. The results indicated that GR was polyhedral. Fat and sugar are evenly distributed in the matrix system. Some of the fat interacts with the starch granules to form a coating that prevents the starch from interacting with the sugar and inhibits the imbibition of water into the starch granules at 50 °C and 70°C. Amylose escapes from the granules and reacts with the sugar solution at a higher temperature of 90 °C, while the free fat acts as a lubricant between the particles. This shows how flour, fat and sugar interact to affect the manufacturing process and the final properties of dodol ulame.